Monitoring of service life consumption for tubular solar receivers: Review of contemporary thermomechanical and damage modeling approaches. (15th September 2021) - Hering, D.; Binder, M.; Schwarzbözl, P.; Schwaiger, R.; Pitz-Paal, R.
Highlights: Review of traditional allowable flux density concept for tubular receiver systems. Outline of novel bottom-up concept for enhanced consideration of operating limits. Systematic, comprehensive review of thermomechanical and damage modeling methods. Assessment as to implementation in bottom-up concept reveals considerable potential. Abstract: Concentrating solar power plays a vital role in the transformation of global energy landscape towards sustainable and environmentally sound energy supply. Currently, tower systems with molten salt tubular receivers are most common in commercial scale applications. Operational optimization of such systems necessitates detailed knowledge of operating limits of receiver components exposed to inhomogeneous solar flux densities of up to 1 MW / m 2 and local salt temperatures of in part more than 600 ° C, fluctuating at various time scales. Traditionally, the operating limits aforementioned are captured in a simplified manner via the top-down concept of allowable flux density. To the authors' view, there is considerable room for improvement over this approach as far as optimization of inherent thermomechanical and damage modeling are concerned. What is more, an alternative bottom-up concept, though implying more stringent requirements on model and processing performance, promises notably increased economic viability essentially due to reduced safety margins in operation and condition-based maintenance strategies. In this paper, essential approaches and assumptions of thermomechanical and damage modeling methods in topical literature are comprehensively discussed and assessed in terms of their potential for the approach outlined to be demonstrated at a pilot scale test facility. As a result, it is concluded that modeling can be substantially improved applying extended analytical methods from the literature. In addition, depending on model complexity and available computational resources, a few heuristic-numerical models are potentially applicable in favor of more detailed thermomechanical modeling regarding i.a. actual receiver geometry and local boundary conditions.